Administration of adipose-derived stromal vascular fraction and platelet rich plasma in dogs with coxofemoral osteoarthritis - Upchurch, David A. (Kansas State University, 2015)
Objective: To evaluate the safety and effect of a single simultaneous intra-articular and intravenous injection of autologous adipose-derived stromal vascular fraction (SVF) and platelet rich plasma (PRP) on coxofemoral osteoarthritis (OA) in dogs. Methods: This was a randomized, double-blind, placebo-controlled prospective pilot trial of simultaneous intra-articular and intravenous SVF and PRP for coxofemoral OA. Dogs with coxofemoral OA causing signs of lameness or discomfort were evaluated by orthopedic exam, visual lameness score, Canine Brief Pain Inventory (CBPI), goniometry, visual analogue scale (VAS), and pressure-sensitive walkway (PSW) at week 0 (baseline), and at 4, 8, 12 and 24 weeks after injection. Joint radiographs were scored at 0 and 24 weeks. Results: Twenty two client-owned dogs with naturally occurring OA of the coxofemoral joints were enrolled (12 placebo-control, 10 SVF-treated). CBPI pain severity scores were lower in the treatment group at 24 weeks compared to the placebo group (p=0.042). The VAS score for the treatment group was significantly greater at 0 weeks than at 4, 8, or 24 weeks (p<0.05). When dogs with low quartile baseline PVF (25th percentile) were compared, the treatment group had statistically higher PVF at all post-injection time points when compared to the placebo group. After SVF injection, fewer dogs in the treated group were lame compared to the control group. Clinical Significance: This study is the first to utilize objective data from PSW as an outcome measure for dogs treated with SVF and PRP for coxofemoral OA. No adverse events were noted. Improvements in some measured parameters in the treated dogs compared to those in the placebo group.
Keywords: Stromal vascular fraction; Mesenchymal stromal cells; Coxofemoral osteoarthritis; Stem cells; Veterinary Medicine (0778)